The - Czinkota, Michael R.
Increasing competition and mounting pressure to boost revenues leave limited growth options for some companies, prompting many to turn a hopeful eye toward international markets. A must-read for anyone interested in breaking into global markets, The Export Marketing Imperative walks readers through the entire exporting process - from beginning to end - offering a wealth of information with its comprehensive coverage of all facets of exporting, including pricing, channel management, marketing plans/strategies, financial environments, and more. An essential resource for entry- and mid-level managers involved in marketing and exporting.